Caesarean delivery mode and its impact on children’s growth and cognitive development - Rini Sekartini; Levina Chandra Khoe (World Nutrition Journal, 2020)
There is an increasing concern on the potential risk of Caesarean birth on child health outcomes. This study aims to present the current available evidences on the effect of Caesarean section on child’s growth and development. Literature searching were done on several online databases to identify articles which discussed the effect of Caesarean birth on child’s body weight, length, nutritional status, cognitive development, memory, learning ability, and intelligence quotient. Several studies showed positive association between Caesarean and risk of overweight and obesity in childhood, adolescence, and adulthood. While, there has not been sufficient evidences to confirm the association between C-section and child’s cognitive outcomes.